Relationship between an indel mutation within the SIRT4 gene and growth traits in Chinese cattle. Issue 4 (2nd October 2019) - Zhang, Qingfeng; Jin, Yunyun; Jiang, Fugui; Cheng, Haijian; Wang, Yafang; Lan, Xianyong; Song, Enliang
Abstract: Growth traits are mainly determined by genetic factors. SIRT4, a class II sirtuin, predominantly acts as an ADP-ribosyltransferase and inhibits fatty acid oxidation. In this study, a total of 1005 cattle belonging to five indigenous Chinese breeds were used to evaluate the relationship between the potential insertions/deletions (indels) within the SIRT4 gene and growth traits. The results revealed that only one intronic variation was present, which showed Hardy–Weinberg equilibrium ( p  > 0.05) in all the populations. The relationship analyses indicated that this indel was significantly associated with growth traits ( p  < 0.05), implying that SIRT4 significantly affects the growth traits. Therefore, the deletion mutation within the SIRT4 gene could be considered as a molecular marker to screen for growth traits in the cattle industry.